Implementasi Pendidikan Karakter pada Anak Keluarga Nelayan Pesisir Pantai - Wulandari, Nurul; Fihayati, Zuyyina (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Character education plays a crucial role in shaping the moral and ethical foundation of the nation's youth. Children residing in coastal areas face complex social and economic challenges, such as limited access to education and negative influences from their surrounding social environment. These educational deficiencies potentially lead to suboptimal cognitive development in coping with various life burdens and pressures in adulthood. Generally, the development of education in several regions of Indonesia has yet to meet the expected quality standards. This study aims to identify the inhibiting factors in the educational process and to explore the character values taught within families, schools, and coastal communities. The research employs a phenomenological approach, enabling an in-depth understanding of the experiences and perceptions of the local community regarding character education. This method facilitates active involvement of parents and teachers as primary agents in character development. Moreover, the local cultural values embedded within coastal societies serve as a strategic foundation to support the implementation of more effective educational programs tailored to the intellectual needs of children in these areas.